Optimasi Polimer Hidroksipropil Metilselulosa K-4M dan Carbopol 940 pada Sediaan Patch Dispersi Padat Meloksikam (Optimization of Hydroxypropyl Methylcellulose K-4M and Carbopol 940 as Polymer in Solid Dispersion Meloxicam Patch) - Indarto Adikusumo; Lidya Ameliana; Dwi Nurrahmanto (UPT Percetakan dan Penerbitan Universitas Jember, 2015)
Meloxicam is non steroidal antiinflammatory drug (NSAID) of the enolic acid class which is widely used in treatment of rheumatoid arthritis. Its adverse effects of oral route, which are nausea dan diarrhea could be evaded by using transdermal patch. Meloxicam is practically insoluble in water, therefore it should be made into solid dispersion.The aims of this research was to determine the effect of combination of hydroxypropyl methylcellulose (HPMC) K-4M and carbopol 940 on the in-vitro drug release and moisture content (MC) and to obtain the optimum formula of those polymers using design experts software. Meloxicam patches were prepared into three formulas based on simplex lattice design with the ratio of HPMC K-4M : carbopol 940 that were 1: 0 ; 0.5 : 0.5 and 0 : 1. The results of this research showed that the patch with HMPC K-4M : carbopol 940 of 0:1 gave the best in-vitro drug release and MC. The optimum formula was HPMC K-4M and carbopol 940 with the ratio of 0 : 1 Keywords: meloxicam, solid dispersion, patch, HPMC, carbopol.